2022
DOI: 10.3389/fnhum.2021.776970
|View full text |Cite
|
Sign up to set email alerts
|

Posture Deficits and Recovery After Unilateral Vestibular Loss: Early Rehabilitation and Degree of Hypofunction Matter

Abstract: Postural instability and balance impairment are disabling symptoms in patients with acute unilateral peripheral vestibular hypofunction (UVH). Vestibular rehabilitation (VR) is known to improve the vestibular compensation process, but (1) its effect on posture recovery remains poorly understood, (2) little is known about when VR must be done, and (3) whether the degree of vestibular loss matters is uncertain. We analyzed posture control under static (stable support) and dynamic (unstable support) postural task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The results of our study show a positive effect of vestibular rehabilitation on postural stability, dizziness intensity, and the self-perception of disability and are in agreement with previous studies, which have demonstrated the benefits of VRT in peripheral unilateral vestibular hypofunction patients [ 1 , 21 ]. A recent Cochrane review [ 5 ] (2015) based on 39 randomized clinical trials and 2441 patients with unilateral vestibular dysfunction, concluded that VRT is a safe and effective treatment and showed the benefits of VRT over no treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study show a positive effect of vestibular rehabilitation on postural stability, dizziness intensity, and the self-perception of disability and are in agreement with previous studies, which have demonstrated the benefits of VRT in peripheral unilateral vestibular hypofunction patients [ 1 , 21 ]. A recent Cochrane review [ 5 ] (2015) based on 39 randomized clinical trials and 2441 patients with unilateral vestibular dysfunction, concluded that VRT is a safe and effective treatment and showed the benefits of VRT over no treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Sample size was estimated using the G-power software (version 3.1.9.2; Heinrich Heine University, Dusseldorf, Germany), using as a reference the data reported by Fraix et al [ 21 ], through a repeated measures ANOVA (between factors). Assuming a significance level of 5%, a power of 80%, an estimated 10% drop-out rate, two groups with four measurements, and an effect size of 0.398, in order to detect differences between the two groups of participants through the study, 30 patients per group were required for a total of 60 study subjects.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that removing visual inputs by closing the eyes or reducing the efficacy of lower-leg proprioceptive inputs by destabilizing the support surface, e.g., by using foam [ 39 ], increases the sensitivity of quiet stance trials toward detecting vestibular deficiencies. Lacour et al also stated that vestibular inputs are more crucial to keep balance in more challenging postural tasks on unstable supports with eyes closed or with moving surroundings [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The instrumental measurement performed using MediPost mobile posturography localized at the L5 level, assessed postural stability in different conditions where the noted grade of improvement varied, as stated in the literature [ 13 , 39 , 40 , 41 ]. The results of condition 4 (standing on foam, eyes closed) were statistically significant for all MediPost measures, which is consistent with other studies [ 5 , 29 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are likely structural differences in the otolith organs of each person, leading to slightly different sensitivities in vestibular sensing across the midline. These small, underlying asymmetries between the left and right otolith organs can cause head tilt, ocular torsion, and skew deviation [1]; postural imbalance [2]; idiopathic scoliosis [3]; and motion sickness [4]. In normal, healthy individuals, this naturally occurring peripheral vestibular asymmetry is compensated for by central processes in a 1G environment; however, symptoms often manifest in situations that challenge the vestibular system.…”
Section: Introductionmentioning
confidence: 99%